A PROSPECTIVE STUDY EXAMINING THE CLINICAL AND FUNCTIONAL OUTCOMES OF ADULTS WITH PROXIMAL HUMERUS FRACTURES TREATED USING A LOCKING COMPRESSION PLATE (LCP): A COHORT STUDY. - Akash, Anant; Agrawal, Nilesh Kumar; Kumar, Alok (Student's Journal of Health Research Africa, 2024)
Background Proximal humerus fractures (PHF) are common, particularly among the elderly, and can significantly impact functional outcomes. The introduction of locking compression plates (LCP) has enhanced the management of these complex fractures by providing stable fixation. The study assessed the clinical and functional results of locking compression plate treatment for PHF in adult patients. Methods Included were 150 patients who had closed proximal humerus fractures that were categorized as 2-, 3-, or 4-part fractures according to NEER guidelines. Using a deltopectoral technique, patients received open reduction and internal fixation with LCP. The Constant-Murley scoring system was used to estimate clinical and functional outcomes, such as pain, daily living activities, range of motion (ROM), and muscle power. There were follow-ups at two weeks, six weeks, three months, six months, and a year. The statistical analysis was carried out with SPSS 23.0. Results The study included participants with a mean age of 38.6 years, 56.7% males​. Significant improvements were observed in all outcome measures. Pain scores decreased from a preoperative mean of 12.5 to 2.1 at one year. Activities of daily living scores improved from 10.3 to 20.0. ROM increased from 22.3 degrees to 80.2 degrees, and muscle power improved from 14.7 to 24.3. Complications were noted in 12% of cases, including infection, hardware failure, nonunion, and subacromial impingement. Statistical analysis confirmed these improvements were highly significant (p < 0.001). Conclusion Locking compression plates effectively improves clinical and functional outcomes for proximal humerus fractures. The significant reduction in pain and enhancement in ROM and muscle power support the use of LCPs in managing these complex fractures. Recommendations Further studies should focus on long-term outcomes and strategies to minimize complications associated with LCPs. Additionally, patient selection criteria and individualized treatment protocols should be optimized based on specific fracture patterns and patient characteristics.